Age-related macular degeneration as a local manifestation of atherosclerosis – a novel insight into pathogenesis - Machalińska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Age-related macular degeneration is the leading cause of irreversible visual impairment and disability among the elderly in developed countries. There is compelling evidence that atherosclerosis and age-related macular degeneration share a similar pathogenic process. The association between atherosclerosis and age-related macular degeneration has been inferred from histological, biochemical and epidemiological studies. Many published data indicate that drusen are similar in molecular composition to plaques in atherosclerosis. Furthermore, a great body of evidence has emerged over the past decade that implicates the chronic inflammatory processes in the pathogenesis and progression of both disorders. We speculate that vascular atherosclerosis and age-related macular degeneration may represent different manifestations of the same disease induced by a pathologic tissue response to the damage caused by oxidative stress and local ischemia. In this review, we characterise in detail a strong association between age-related macular degeneration and atherosclerosis development, and we postulate the hypothesis that age-related macular degeneration is a local manifestation of a systemic disease. This provides a new approach for understanding the aspects of pathogenesis and might improve the prevention and treatment of both diseases which both result from ageing of the human body.